2012
DOI: 10.1104/pp.112.204016
|View full text |Cite
|
Sign up to set email alerts
|

Misexpression of a Chloroplast Aspartyl Protease Leads to Severe Growth Defects and Alters Carbohydrate Metabolism in Arabidopsis    

Abstract: The crucial role of carbohydrate in plant growth and morphogenesis is widely recognized. In this study, we describe the characterization of nana, a dwarf Arabidopsis (Arabidopsis thaliana) mutant impaired in carbohydrate metabolism. We show that the nana dwarf phenotype was accompanied by altered leaf morphology and a delayed flowering time. Our genetic and molecular data indicate that the mutation in nana is due to a transfer DNA insertion in the promoter region of a gene encoding a chloroplast-located aspart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 92 publications
0
33
0
Order By: Relevance
“…Because we routinely supply Suc to MS plates, we suspected that Suc may up-regulate the expression of GLK1. Consistent with this idea, it has been shown that carbohydrate metabolism in chloroplasts affects the expression of GLK1 in the nucleus (Paparelli et al, 2012). Hence, we tested the effect of Suc on the accumulation of GLK1.…”
Section: Production Of Specific Antibodies Against Glk1 Proteinmentioning
confidence: 67%
“…Because we routinely supply Suc to MS plates, we suspected that Suc may up-regulate the expression of GLK1. Consistent with this idea, it has been shown that carbohydrate metabolism in chloroplasts affects the expression of GLK1 in the nucleus (Paparelli et al, 2012). Hence, we tested the effect of Suc on the accumulation of GLK1.…”
Section: Production Of Specific Antibodies Against Glk1 Proteinmentioning
confidence: 67%
“…Total RNA Extraction and Quantitative PCR RNA extraction, removal of genomic DNA, cDNA synthesis, and quantitative RT-PCR analyses were performed as described previously (Paparelli et al, 2012). GAPDH and 40SrRNA were used as reference genes.…”
Section: Plant Materialsmentioning
confidence: 99%
“…Frozen samples were homogenized then extracted in perchloric acid, as previously described (Paparelli et al, 2012). Glc, Suc, Fru, and starch were measured enzymatically on the neutralized supernatant (soluble sugars) (Guglielminetti et al, 1995) and the insoluble pellet (starch) (Critchley et al, 2001).…”
Section: Extraction and Analysis Of Carbohydratesmentioning
confidence: 99%
“…Type II metacaspase from wheat leaves (TaeMCAII) was modeled in silico, cloned and characterized (Piszczek et al 2011;Piszczek et al 2012). Studies of Arabidopsis thaliana dwarf mutant, impaired in carbohydrate metabolism, enabled characterization of NANA, chloroplastlocated, aspartic proteinase (Paparelli et al 2012).…”
Section: Resultsmentioning
confidence: 99%